Introduction of the hierarchical self-assessment model for upgrading digital school strategy - Čampelj, Borut (Revija za ekonomske in poslovne vede, 2020)
Headmasters and teachers have different perceptions of school informatisation, and the consequences are unsystematic planning and implementation of activities at individual and school level. This paper presents a comprehensive hierarchical self-assessment model for school informatisation. The designed indicators are organised hierarchically as a tree, from more complex to more simple. Sub-indicators at the highest level are: "School and the environment", "Teachers and on-line communities" and "Students and the environment". The tree representing the indicators has a complexity of up to 10 levels and is highly diversified with 106 leaves (basic indicators). The user self-assesses the current situation at the school by choosing one of the four possibilities for each basic indicator. Then the model itself determines the values of indicators at higher levels. The model was also tested in schools during four-hour workshops. The participants (54) assessed the model as a promising qualitative tool for understanding comprehensive informatisation and objectively determining the current school situation, which could lead to a higher level of further planning and implementation of school informatisation.
Keywords: hierarchical multi-attribute decision model; hierarhični večparametrični odločitveni model; informatisation; informatizacija; modeliranje; modelling; samoevalvacija; school; self-assessment; šola